Newly discovered uranium mineralization at ~2.0 Ma in the Menggongjie granite-hosted uranium deposit, South China - Luo, Jin-Cheng; Hu, Rui-Zhong; Fayek, Mostafa; Bi, Xian-Wu; Shi, Shao-Hua; Chen, You-Wei (Journal of Asian earth sciences, 2017)
[Display omitted] •SIMS uraninite U-Pb dating yields the age of 1.9±0.7Ma.•Uranium mineralization at the MGJ deposit is synchronous with the Quaternary volcanic activities in the region.•The MGJ deposit might represent the youngest granite-hosted uranium deposit reported so far in South China. The southeastern part of the Nanling metallogenic province, South China contains numerous economically important granite-hosted, hydrothermal vein-type uranium deposits. The Miao’ershan (MES) uranium ore field is one of the most important uranium sources in China, hosts the largest Chanziping carbonaceous-siliceous-pelitic rock-type uranium deposit and several representative granite-hosted uranium deposits. The geology and geochemistry of these deposits have been extensively studied. However, accurate and precise ages for the uranium mineralization are scarce because uranium minerals in these deposits are usually fine-grained, and may have formed in several stages, thus hindering the understanding of the uranium metallogenesis of this province. The Menggongjie (MGJ) uranium deposit is one of the largest granite-hosted uranium deposits in the MES ore field. Uranium mineralization in this deposit occurs at the central part of the MES granitic complex, accompanied with silicification, fluorination, K-metasomatism and hematitization. The ore minerals are dominated by uraninite, occurring in quartz or fluorite veinlets along fractures in altered granite. In-situ SIMS U-Pb dating on the uraninite yields the U–Pb isotopic age of 1.9±0.7Ma, which is comparable to the chemical U-Th-Pbtol uraninite age of 2.3±0.1Ma. Such ages agree well with the eruption ages of the extension-related Quaternary volcanics (2.1–1.2Ma) in South China, suggesting that the uranium mineralization have formed at an extensional setting, possibly related to the Quaternary volcanic activities. Therefore, our robust, new dating results of the MGJ uranium deposit make it the youngest granite-hosted uranium deposit reported so far in South China and the mineralization event represents a newly identified mineralization epoch.